Effects of sea buckthorn (Hippophae rhamnoides L.) on factors related to metabolic syndrome: A systematic review and meta‐analysis of randomized controlled trial. (31st August 2022) - Geng, Yaping; Wang, Jing; Chen, Ke; Li, Qianwen; Ping, Zhiguang; Xue, Ran; Zhang, Shenshen
Abstract: The purpose of this meta‐analysis is to explore whether the supplement of sea buckthorn affects the factors related to metabolic syndrome. The related RCTs from five databases were systematically searched and comprehensively random effects model was used to calculate SMD and 95% CI. The Cochrane deviation risk tool was used to evaluate the deviation risk. Fifteen studies were involved in the meta‐analysis. First, sea buckthorn supplementation reduced triglycerides [−0.722 (−1.129, −0.316); p  < .001], total cholesterol [−0.345 (−0.639, −0.051); p  = .021], low density lipoprotein cholesterol [−0.396 (−0.755, −0.037); p  = .031], and increased high density lipoprotein cholesterol [0.370 (0.056, 0.684); p  = .021] in overall subjects. Second, subgroup analysis showed that sea buckthorn supplementation reduced lipids only in people with abnormal lipid metabolism. Third, sea buckthorn had no effect on blood sugar, blood pressure, and BMI of the overall subjects. Sea buckthorn may affect the lipid metabolism in circulation, but it cannot affect blood glucose, blood pressure, and BMI. These indicators are closely associated with metabolic syndrome. This study may contribute to the development and utilization of sea buckthorn, and may provide a new and safer way for the prevention and treatment of metabolic syndrome. The limitation of this study is high heterogeneity, even if subgroup analysis is used. However, more clinical studies are needed to determine the real effect of sea buckthorn on metabolic syndrome.